Una aproximación al mejoramiento productivo de la etapa de acabados en un proyecto de construcción de vivienda; caso de estudio (2020)
Although the construction sector in the last decade has grown in Colombia, situations are currently being perceived to disadvantage this market, projecting erosion in its growth. Some organizations have realized that it is relevant to develop more efficient tactic models of operation, which improve the price level, accelerating delivery times and thus seeking new competitive advantages on the market. In view of this reality, the purpose of this investigation is focused on determining new practices from a valuation that will lead to neutralizing or decreasing the sources of waste and cost - of - Post costs, by reprocessing along the value stream of the "housing construction process in a construction project located in Neiva city